Approaches of Fast Moving Consumer Good Brand Manufacturers towards Product Development. Safe players versus Productors: Implications for Retailers' Management of Manufacturer Relations - Bodil Stilling Blichfeldt (University of Southern Denmark, Department of Environmental and Business Economics (IME), 2004)
Drawing on a qualitative study of fast moving consumer good manufacturers management of development of line extensions, the purpose of this paper is to pinpoint implications of such management for manufacturers relations with retailers. Especially, the study suggests that manufacturers emphasising brands are likely to choose a stand alone approach towards retailers whilst manufac-turers emphasising products are more likely (1) to collaborate with retailers whilst developing line extensions and (2) to engage in private label product de-velopment and production. Apart from the fact that the study suggests retailers to influence manufacturers levels of innovativeness in relation to line exten-sions, the study further suggests that manufacturers can be divided into two dif-ferent groups on the basis of their line extension development activities. On the basis of these two different approaches, the paper points to implications for re-tailers management of manufacturer relations.
Keywords: 330; Konsumgüterindustrie; Lieferanten-Kunden-Beziehung; Markenartikel